2013
DOI: 10.1080/07448481.2013.831352
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Risky Drinking Behaviors and Motivations for Alcohol Use in a College Sample

Abstract: Drinking to enhance positive affect may be the most salient motivation for drinking related to pregaming and drinking games for college drinkers. Findings have implications for interventions tailored to students engaging in various heavy drinking practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…Using a large multisite and multiethnic college student sample, Zamboanga, Schwartz, Van Tyne, et al (2010) found that high-frequency gamers who drank elevated amounts of alcohol while gaming reported relatively more negative alcohol-related outcomes compared with (a) high- and low-frequency gamers who consumed low amounts of alcohol while gaming, and (b) low-frequency gamers who drank high amounts of alcohol while gaming. Other research has found a positive association between the number of drinks consumed while gaming and negative alcohol-related outcomes (Sheehan, Lau-Barraco, & Linden, 2013). In short, there may be factors other than frequency of participation that can affect gamers’ risk for experiencing negative alcohol-related outcomes (cf.…”
Section: Review Of Current Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…Using a large multisite and multiethnic college student sample, Zamboanga, Schwartz, Van Tyne, et al (2010) found that high-frequency gamers who drank elevated amounts of alcohol while gaming reported relatively more negative alcohol-related outcomes compared with (a) high- and low-frequency gamers who consumed low amounts of alcohol while gaming, and (b) low-frequency gamers who drank high amounts of alcohol while gaming. Other research has found a positive association between the number of drinks consumed while gaming and negative alcohol-related outcomes (Sheehan, Lau-Barraco, & Linden, 2013). In short, there may be factors other than frequency of participation that can affect gamers’ risk for experiencing negative alcohol-related outcomes (cf.…”
Section: Review Of Current Literaturementioning
confidence: 94%
“…As evidenced in this review, there are other important aspects to drinking games participation that should be considered, including participants’ BAC (Cameron et al, 2011), participants’ perceived tolerance (Ehret, LaBrie, & Hummer, 2012), the type of drinking games played (LaBrie et al, 2013), reasons for playing drinking games (Johnson & Sheets, 2004), and the negative consequences that result directly from gaming (Borsari et al, 2013). Given these nuances, the development of a standardized, comprehensive measure of drinking games involvement as well as a standardized definition of drinking games would be a very important advancement in the field (Borsari et al, 2013; Sheehan et al, 2013; Zamboanga, Horton, et al, 2007; Zamboanga et al, 2013). …”
Section: Future Directions For Drinking Games Researchmentioning
confidence: 99%
“…Recent research has demonstrated that participation in drinking games continues to be highly prevalent among college students (1,2). Drinking games have yet to be formally defined, but a common conceptualization is that: (a) they are social drinking activities, (b) involve some kind of mental and/or physical task, and (c) have a specific set of rules that promote elevated alcohol consumption (see 3).…”
Section: Introductionmentioning
confidence: 99%
“…These types of reasons are categorized as social and enhancement motives, which indicate that pregaming is motivated by the desire to obtain positive reinforcement via external or internal means, respectively (Cox & Klinger, 1988). Social motives have been found to predict pregaming behavior over and above other motives (Pedersen & LaBrie, 2007), while enhancement motives have been found to explain a third of the variance in alcohol-related problems encountered by pregamers (Sheehan, Lau-Barraco, & Linden, 2013). Pregamers also report drinking more often for coping motives than do nonpregamers .…”
mentioning
confidence: 99%